IMPLEMENTATION OF 5C BASED FINANCING IN BMT ALFA DIRHAM MANDIRI - Akrom, Maulana; Fatahillah, Mubarok; Husnaeni, Nurul; Adawiyah, Robiaatuul (Penerbit Lafadz Jaya, 2022)
This research is to analyze the implementation of 5C-based financing (Character, Capacity, Capital, Collateral, Condition) at BMT Alfa Dirham Mandiri, aiming to obtain data regarding planning, implementation, and assessment of 5C principle-based financing at BMT Alfa Dirham Mandiri. The type of research used is qualitative. The data collection techniques used were interviews, observation, and documentation. The data source for this research is primary, namely collected through direct interviews. This research shows that BMT Alfa Dirham Mandiri, as a sharia microfinance institution, applies financing based on murabahah, mudharabah, kafalah bil ujrah, wadiah and musyarakah contracts. Financing is carried out according to strict SOPs, from application to disbursement of funds. The 5C principle (Character, Capacity, Capital, Collateral, Condition of Economy) is applied to assess the feasibility of financing, with collateral only for financing above 3 million. Implementation of the 5C principles reduces the risk of financing problems. The research results show that: 1). Financing planning includes applying for financing, assessing financing. 2). implementation of financing through various contracts such as murabahah, mudhorobah, musyarakah. Kafalah bil ujrah, and wadiah. 3) The 5C principles in BMT Alfa Dirham Mandiri are as a financing assessment tool, the 5C principles include character, capacity, capital, collateral, and economic conditions.